Cognitive and Emotional Engagement in Stoichiometry Learning: A Correlational Study - Waviza; Erlina; Eni Mayasari (Universitas Pendidikan Mandalika, 2026)
The purpose of this study was to measure the strength of the relationship between students’ cognitive and emotional engagement in stoichiometry learning. This research employed a descriptive quantitative approach, including descriptive analysis and correlational analysis. The participants consisted of 70 eleventh-grade students enrolled in the science-track chemistry course, drawn from two classes: Grade XI Chemistry 1 and Grade XI Chemistry 2. Data were collected using a four-point Likert-scale questionnaire measuring cognitive and emotional engagement, as well as through observations, semi-structured interviews, and documentation. The results showed that: (1) students’ cognitive engagement was categorized as very high (13%), high (34%), low (43%), and very low (10%); (2) students’ emotional engagement was categorized as very high (20%), high (16%), low (53%), and very low (11%); (3) the correlation test between cognitive and emotional engagement was significant (0.000 < 0.05), indicating a positive relationship; and (4) the strength of the relationship between cognitive and emotional engagement, as indicated by Spearman’s rho, was 0.447, which represents a moderate level of correlation. Therefor, higher cognitive engagement is associated with higher emotional engagement, and vice versa.